2021
DOI: 10.3390/app112311442
|View full text |Cite
|
Sign up to set email alerts
|

PGPB Improve Photosynthetic Activity and Tolerance to Oxidative Stress in Brassica napus Grown on Salinized Soils

Abstract: Soil salinization, one of the most common causes of soil degradation, negatively affects plant growth, reproduction, and yield in plants. Saline conditions elicit some physiological changes to cope with the imposed osmotic and oxidative stresses. Inoculation of plants with some bacterial species that stimulate their growth, i.e., plant growth-promoting bacteria (PGPB), may help plants to counteract saline stress, thus improving the plant’s fitness. This manuscript reports the effects of the inoculation of a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 72 publications
(115 reference statements)
5
12
1
Order By: Relevance
“…There are many controversies about the effect of salinity on the amount of chlorophyll. Many researchers have reported that salinity reduces chlorophyll in salt-sensitive plants and increases it in salt-tolerant plants [38][39][40]. Our data agree with those showing a decrease of chlorophyll in plants exposed to salt stress and non-primed [38], while priming treatment with PAs improved the tolerance of tomato plants to salt stress with respect to chlorophyll maintenance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are many controversies about the effect of salinity on the amount of chlorophyll. Many researchers have reported that salinity reduces chlorophyll in salt-sensitive plants and increases it in salt-tolerant plants [38][39][40]. Our data agree with those showing a decrease of chlorophyll in plants exposed to salt stress and non-primed [38], while priming treatment with PAs improved the tolerance of tomato plants to salt stress with respect to chlorophyll maintenance.…”
Section: Discussionsupporting
confidence: 91%
“…PAs might be positive activators of non-enzymatic protective pathways, reducing the production of radical species, such as DPPH, ferric tripyridyl-triazine or potassium ferrocyanide. To increase antioxidant activity, plants can also enhance the synthesis of osmolytes, such as proline, and secondary metabolites, such as phenols and flavonoids [26,39,40], which are species-specific and associated with plant protection against both abiotic and biotic stresses. Although the synthesis of secondary metabolites increases when plants are grown under salt stress conditions, many studies pay particular attention to only a few target compounds.…”
Section: Discussionmentioning
confidence: 99%
“…After exposure to salinity, it is usual that the photosynthetic rate decreases in response to a decline in leaf area, gas exchange, and also feedback suppression of unused photosynthates (Ilangumaran and Smith, 2017). As observed in the present study, under the effect of salinity, PGPB led to a higher photosynthetic efficiency in licorice plants (by increasing osmolyte production, reduction in membrane damage, higher antioxidant activity, all to protect photosynthetic apparatus) (Rossi et al, 2021), as were similar cases observed in maize plants (Zea mays L.) (Hafez et al, 2021) and pistachio trees (Pistacia vera) (Khalilpour et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…Although, in our study, an increase in non-photochemical quenching was observed when plants were inoculated with PGPB, other studies have found contrasting results that were also associated with a beneficial effect of the bacteria [ 31 ]. Because of the great variability in the responses of plants to water deficit, both an increase and a decrease in heat dissipation can indicate a positive effect of PGPB inoculation.…”
Section: Discussioncontrasting
confidence: 74%